The structure of Prunus avium L. crops and their importance for pollinating insects in seed orchards in Poland - Kęsy, Mateusz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2021)
The functioning of forests in Poland is often associated with a productive role and the production of wood-based raw materials, disregarding the need to protect forest environments. In practice, the approach to the protection of nature and animals, including insects in forest areas, has changed in recent decades. Many researchers still point to the need to protect the processes taking place in forest environments. Actions are being taken to reduce monocultures in forests and to increase the biodiversity of plants and animals living among crops. A good example described in this paper is the relationship between seed plantations and insects. These relationships may have a positive effect on the fruiting process and seed production in selected tree species. This paper presents an example of the relationship between wild bees and Prunus avium L. seed plantations as an example of a positive relationship in which humans as well as pollinating insects can benefit. The structure and size of Prunus cultivation in Poland are described and the hitherto harvest of seeds is analysed. The elements of the biology of the Prunus species, important for the process of pollination of flowers by insects are also indicated. The study also indicates ways to protect bees in the forest environment.